[PP.04.24] THE IMPACT OF HYPERTENSION ON QT DISPERSION AND ECHOCARDIOGRAPHIC PARAMETERS IN PATIENTS WITH ANGINA PECTORIS. (September 2017) - Stoickov, V.; Ilic, M. Deljanin; Stoickov, M.; Tasic, I.; Nikolic, M.; Mitic, S.
Abstract : Objective: Introduction: QT dispersion (QTd) is a measure of inhomogeneous repolarization of myocardium and is used as an indicator of arrhythmogenicity. According to the values of QTd can identify coronary patients who are at high risk of cardiac death and sudden cardiac death. Objective: The aim of this study was to investigate the effect of hypertension on QT dispersion and echocardiographic parameters in patients with angina pectoris. Design and method: The study included 113 patients with angina pectoris (average age 57.2 years), of which 78 were with hypertension, and 35 were without arterial hypertension. There were no significant differences in age and gender between the two groups of patients. In all subjects exercise stress test on a treadmill according to the Bruce protocol and echocardiographic examination were performed and from standard ECG corrected QT dispersion (QTdc) and QTd was calculated. Results: Patients with angina pectoris and hypertension had significantly higher values of QTd (55.1 ± 17.1 vs 42.8 ± 19.5 ms; p < 0.01) and QTdc (59.2 ± 20.0 vs 45.5 ± 18.1 ms; p < 0.001) compared to those without arterial hypertension. Also, patients with angina pectoris and hypertension had significantly higher values of the thickness of the interventricular septum (12.1 ± 2.1 vs 10.8 ± 1.7 mm; p < 0.005), left ventricle posterior wall thickness (10.9 ± 1.5 vs 9.2 ± 1.4 mm; p < 0.001) and left atrium diameter (40.9 ± 4.8 vs 37.3 ± 5.4 mm; p < 0.005) compared to those without hypertension. Patients with angina pectoris and arterial hypertension have higher values of the left ventricular end-diastolic diameter (54.1 ± 5.8 vs 53.7 ± 7.1 mm; p-NS), and left ventricular end-systolic diameter (36.6 ± 6.1 vs 35.8 ± 6.9 mm; p-NS) and lower values of left ventricular ejection fraction (60.9 ± 11.2 vs 63.6 ± 11.9%; p-NS), but the differences were not statistically significant. Conclusions: The study demonstrated that patients with angina pectoris and hypertension have significantly higher values of QT dispersion parameters, thickness of the left ventricle walls and left atrium diameter in comparison to those without hypertension.